Studi Komparatif Hasil Belajar Bahasa Indonesia Secara Luring Dengan Daring Siswa Kelas V SD - Atika Atika; Abdul Hafid; Sudirman Sudirman (Universitas Negeri Makassar, 2021)
This thype of research is ex-post facto research by conducting comparative. A comprative study was conducted because of problems with student online learning outcomes which have decreased since transfer of learning from offlineto online. The population and research sample were all students of class V SD Gugus II, Sabbangparu District, Wajo Regency. The number of population and sample are the same, namely as many as 66 students, and for the technique of determining the offline data sample using online cluster random sampling. Data collection techniques used were documentation and interview. The data analysis technique using independent sample t-test. The results showed that the price of tcount > ttable so that the hypothesis H1 was accepted and H0 was rejected. The hypothesis is that there are differences in learning outcomes of Indonesian Language Offline and Online students of class V SD. Study conclusion there was a difference between the results of learning Indonesian offline and online students of Class V SD Gugus II, Sabbangparu sub-distric, Wajo distric. After knowing the differences in student learning outcomes offline and online, the teacher must have innovations to harmonize the learning process carried out both offline and online so that the learning outcomes achieved by student are as good.